Impact of Live Streaming Quality on Impulsive Buying Behavior: Mediating Effect of Shopper Motivation - Farah Salsabila; Fatchur Rohman; Raditha Dwi Vata Hapsari Hapsari (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study focuses on the influence of live streaming quality on impulsive buying behavior, considering the mediating role of hedonic motivation and utilitarianism among Generation Z consumers in Malang City. This study responds to the phenomenon of declining online purchases that is directly proportional to the decline in impulsive buying, even though most e-commerce consumers access and make purchases through live streaming features. A quantitative approach and SEM-PLS analysis on 170 respondents found that live streaming quality significantly influences impulsive buying, both directly and through motivational mediation. The test results indicate that both hedonic and utilitarian motivations mediate the relationship between external factors (live streaming quality) and impulsive buying. This study utilizes the Self-Determination Theory (SDT) framework to explain how intrinsic and extrinsic motivations influence consumer behavior. The resulting model demonstrates strong predictive power with an R² value of 76.2%, indicating the factors' relevance of the factors to impulsive purchasing behavior in live streaming-based e-commerce.